Oral step-down vs full-course intravenous antibiotic therapy for infective endocarditis: Protocol for a systematic review and meta-analysis - Jose D. Cruz-Cuevas; Julián Andrés Amador Bedoya; María Paula Méndez Gaitán; María Camila Ramírez; Javier González Quiroga; Adelaida Rodríguez Villegas; Antonia Sanín Reyes (PLoS ONE, 2026)
Background Infective endocarditis (IE) is a life-threatening condition traditionally managed with prolonged intravenous (IV) antibiotic therapy. However, sequential oral antibiotic therapy has emerged as a promising alternative in selected patients, potentially reducing hospital stay, adverse events, and healthcare costs. While the POET trial demonstrated non-inferiority of oral step-down therapy in a narrow subset of patients with left-sided IE, broader applicability remains uncertain. Observational studies and recent meta-analyses have yielded heterogeneous and inconclusive results, underscoring the need for a comprehensive synthesis of current evidence. Methods This protocol outlines the methodology for a systematic review and meta-analysis comparing the effectiveness and safety of sequential oral antibiotic therapy versus full-course IV therapy in adult patients with bacterial IE. We will include randomized controlled trials and observational comparative studies enrolling adults diagnosed with IE by Duke criteria, clinical judgment, or histopathological confirmation. The primary outcomes are all-cause mortality and clinical cure; secondary outcomes include relapse, unplanned cardiac surgery, embolic events, hospital length of stay, and adverse events. Searches will be conducted in MEDLINE, Embase, CENTRAL, and LILACS, with no restrictions on publication date or language. Risk of bias will be assessed using RoB 2 and ROBINS-I tools. Data synthesis will follow Cochrane guidelines, and certainty of evidence will be evaluated using the GRADE approach. Discussion This review will provide a rigorous and up-to-date synthesis of the evidence on oral step-down therapy in IE, addressing populations underrepresented in prior trials. The findings will inform clinical decision-making, guideline development, and future research on optimizing antibiotic strategies for IE. Systematic review registration PROSPERO registration number: CRD420251104423